2006
DOI: 10.1159/000094715
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Ovalbumin Exposure Attenuates Airway Hyperresponsiveness and T Cell Function in Mice

Abstract: Background: Continuous exposure of sensitized mice to an innocuous antigen, such as OVA, does not lead to chronic airway eosinophilia, but induces antigen unresponsiveness and resolution of the inflammatory response. In this study we explored mechanisms underlying attenuation of the airway inflammatory response, assessed whether the phenomenon is strain-specific, and determined its consequences to airway physiology. Methods: Mice were sensitized and exposed to OVA for two and four weeks. Analysis involved BAL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…This suggests that HDM might be the allergen driving this aspect of the inflammatory response at 24 hours following the final allergen exposure. A possible explanation for the greater degree of eosinophilic inflammation in the HDM-exposed mice, compared with the OVA-exposed mice, might be that the protease activity of the HDM extracts gives this aeroallergen its antigenic nature and prevents the development of tolerance (Fattouh et al, 2005;Johnson et al, 2004;Kheradmand et al, 2002), which is known to occur with chronic exposure to OVA (Swirski et al, 2002;Swirski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that HDM might be the allergen driving this aspect of the inflammatory response at 24 hours following the final allergen exposure. A possible explanation for the greater degree of eosinophilic inflammation in the HDM-exposed mice, compared with the OVA-exposed mice, might be that the protease activity of the HDM extracts gives this aeroallergen its antigenic nature and prevents the development of tolerance (Fattouh et al, 2005;Johnson et al, 2004;Kheradmand et al, 2002), which is known to occur with chronic exposure to OVA (Swirski et al, 2002;Swirski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, continuous exposure to OVA for several weeks in animals that have been sensitized previously with an aluminum-based adjuvant conjugated to OVA causes a decline in, and complete cessation of, the airway inflammatory response rather than an increase in, or maintenance of, the inflammation (Swirski et al, 2002;Swirski et al, 2006). Although it appears that the inflammatory aspect of the response in dual challenged animals may be explained entirely by the observed response to HDM alone, it is important to point out that exposure to HDM followed by exposure to OVA has been shown to prevent the tolerance associated with OVA alone (Fattouh et al, 2005).…”
Section: Dmmbiologistsorg 278mentioning
confidence: 99%
“…This model shares several features with other postsensitization models of inhalation tolerance developed in mice (15,16) and rats (14), including suppressed recruitment of effector CD4 + T cells and eosinophils into the airways and attenuated airways hyperresponsiveness through the promotion of Treg activity. We found that both CD11b hi CD103 2 and CD11b lo CD103 + AMDC captured inhaled OVA in vivo during the early onset of allergic inflammation, and that induction of inhalation tolerance markedly inhibited the capacity of AMDC subsets for aeroallergen capture.…”
Section: Endritic Cells (Dc)mentioning
confidence: 80%
“…A variety of rodent models have demonstrated this phenomenon, including passive exposure to aeroallergen before sensitization or chronic exposure to aeroallergen after sensitization, with Treg induction and activity implicated in the maintenance of tolerance in both cases (11)(12)(13)(14)(15)(16). In contrast, repeated inhalation of complex Ag extracts such as house dust mite leads to persistent inflammation and remodeling in some cases (17), presumably as a consequence of their inherent TLR or proteolytic activity.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…[15][16][17][18] This phenomenon, known as local inhalational tolerance, is characterized by local resolution of allergic airway inflammation because it courses along with persistent systemic IgE production. [19][20][21] Various studies using this model suggested different mechanisms for the resolution of allergic inflammation such as the emergence of Foxp3 þ CD25 þ CD4 þ regulatory T (Treg) cells, [22][23][24] or regulatory B cells, 25 or a population of transforming growth factor (TGF)-b 1 -expressing macrophages. 26 Although these studies were well conducted, none of them compared the specific contribution of these different regulatory pathways.…”
Section: Introductionmentioning
confidence: 99%